Handling Minor Crimes Through Restorative Justice As A Form Of Efficiency In The Makassar Police - Alqadri Syarif, Andi Muhammad; Fachri, Muhammad; Bin Fatahillah, Irfan Marhaban (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study explores the implementation of restorative justice as a form of efficiency in handling misdemeanor cases at the Makassar Police. The need for humane and efficient justice for the handling of minor crimes, where the restorative approach is an alternative that is increasingly encouraged. The purpose of this study is to analyze the handling of misdemeanor crimes through restorative justice as a form of efficiency in the Makassar Police by identifying the implementation of restorative justice for misdemeanor cases and the factors that hinder their success. The method used is a qualitative approach with a descriptive design, which involves data collection through literature studies and interviews related to the implementation of restorative justice in the institution. The results of the study show that the use of restorative justice is able to accelerate the resolution of minor criminal cases, increase the sense of justice for victims and perpetrators, and reduce the burden on the formal justice system. However, its implementation is still hampered by several factors such as abuse of authority from investigators and public resistance